Analysis of Adverse Drug Reaction Reports from a Public Hospital in Shanxi Province in 2022 - Zhang XJ; Zhou JG; Pan M; Yuan W; Gao B (Dove Medical Press, 2023)
Xiao-Jie Zhang,1 Jian-Guo Zhou,1 Miao Pan,1 Wei Yuan,2 Bo Gao1 1Department of Pharmacy, General Hospital of Yangquan Coal Industry Group, Yangquan, People's Republic of China; 2Department of Oncology and Interventional Radiology, Yangquan Hospital of Shanxi Medical University, Yangquan, People's Republic of ChinaCorrespondence: Wei Yuan, Department of Oncology and Interventional Radiology, Yangquan Hospital of Shanxi Medical University, No. 218 of North Street, Mining District, Yangquan, 045000, People's Republic of China, Tel/Fax +86 131 6212 9135, Email lvyingyw@126.com Bo Gao, Department of Pharmacy, General Hospital of Yangquan Coal Industry Group, Yangquan, People's Republic of China, Tel/Fax +86 139 3539 8859, Email gaobo12@um.gt.cnObjective: Through analyzing the characteristics and influencing factors of adverse drug reactions/adverse events (ADR/ADE) in a hospital to promote rational drug use in the clinic.Methods: A total of 1221 ADR/ADE reports collected from a hospital in 2022 were retrieved through the National Adverse Drug Reaction Monitoring Center. The effective reports were screened according to the Guiding Principles for Collection and Reporting of Individual Adverse Drug Reactions, and classified the standardized drugs. The systems/organs and main clinical symptoms affected by ADR/ADE were classified according to the WHO Glossary of Adverse Drug Reaction Terms. The severity, age and gender, occupational distribution, drug category, route of administration, drug dosage form, system/organ involved, and main clinical symptoms of ADR/ADE reports were analyzed.Results: Among 1221 ADR/ADE reports, 890 cases (75.27%) reported by doctors; 144 cases (11.79%) were serious; Precisely 49.22% of ADR/ADE occurred in patients aged 51 to 70 years old; The highest incidence of adverse reactions was 636 cases (52.09%) by intravenous infusion, 406 cases (33.25%) by oral administration. The top categories of reported cases were anti-infective drugs (29.40%) and anti-tumor drugs (27.52%); Systems/organs involved in ADR/ADE were mainly the skin and its accessories (24.96%) and blood system (21.35%). 166 cases were cured, 893 cases were symptomatic, 160 cases were unknown, and 2 cases had sequelae.Conclusion: The occurrence of ADR/ADE is related to many influencing factors such as age, drug categories, and route of administration. Therefore, it is recommended that hospitals strengthen the monitoring of ADR/ADE, especially the elderly, anti-infective drugs and intravenous administration.Keywords: adverse drug reactions, adverse events, report analysis, the rational use of drugs